A side effect of a university boom: rising incidence of overeducation among tertiary educated workers in Poland - Baran, Jan (Economics and Business Review, 2018)
This paper analyses changes in overeducation incidence in Poland in 2006‑2014. It finds that a rise in number of tertiary educated workers outpaced an increase in number of jobs requiring tertiary education, which resulted in a substantial growth of overeducation incidence. The overeducation increase was driven mainly by mild overeducation rather than severe overeducation. Overeducated workers are usually young with little job experience. Women are found at lower risk of severe overeducation compared to men, but relatively more at risk of mild overeducation. A low risk of overeducation is associated with having studied technical and health programmes.